STRESS AND BURNOUT AMONG INFORMATION TECHNOLOGY (IT) EMPLOYEES - J, Aravind (International Journal of Psychosocial Rehabilitation, 2020)
Software industry is one sector, which is affected profoundly by stress and professionals serving these organizations are often observed under huge stress. Software professional’s nature of job is highly time-bound, client oriented and technology intensive. Stress is the emotional feeling of an individual to fight or flee when faced with a problem or demand. Stress is the perception of discrepancy between environmental demands and individual capacities to fill these demands. When individuals face stress due to various conditions of their occupation and fail to cope with stress, it results into burnout. The employee who suffers burnout becomes disorganized, disoriented and it may result into harmful psychological and physiological effects. The present study is conducted to measure the level of stress and burnout among IT employees, to analyze the various dimensions of burnout, to identify the causes of stress and to identify various measures for reducing stress and burnout. The study is conducted among the IT employees working in Cyper Park, Calicut District. A sample of 200 IT employees is selected by using stratified random sampling method based on gender. The study revealed that the IT employees in Cyber Park experienced only medium and moderate level of stress. The most serious cause is ‘Work overload’ and least serious is ‘Working Conditions.